DINAMIKA PEMILIHAN KEPALA DAERAH LANGSUNG DI PROVINSI SULAWESI TENGGARA - Teguh Setyabudi; Sampara Lukman; Aries Djaenuri; Khasan Effendy (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
This study discusses the dynamics of direct regional head elections at the provincial level with a case study of the election of the Governor and Deputy Governor of Southeast Sulawesi Province in 2018. This study is not necessarily interpreted as a change in direct local elections to be indirect, but rather as a middle way in making policies in the future. will come. This study begins with a review of various direct election problems as a form of evaluation. Thus, the implementation of direct elections can improve the quality of democracy at the local and national levels. Further research is highly recommended after this study.